Operation of photon diagnostic imagers for beam commissioning at the European XFEL. (19th August 2019) - Koch, Andreas; Risch, Johannes; Freund, Wolfgang; Maltezopoulos, Theophilos; Planas, Marc; Grünert, Jan
Abstract : Photon diagnostic imagers provide information on the X‐ray free‐electron laser beam along the photon‐transport path from the undulators up to the scientific instruments. Abstract : X‐ray photon beam diagnostic imagers are located at 24 positions in the European XFEL beam transport system to characterize the X‐ray beam properties, and to give feedback for tuning and optimization of the electron acceleration and orbit, the undulators, and the X‐ray optics. One year of commissioning allowed experience to be gained with these imagers, which will be reported here. The sensitive Spontaneous Radiation imager is useful for various investigations in spontaneous radiation mode: for undulator adjustments and for low‐signal imaging applications. The high‐resolution Free‐Electron Laser imager, 10 µm spatial resolution, is extensively used for the monitoring of beam position, spot size and shape, gain curve measurements, and also for beam‐intensity monitoring. The wide field‐of‐view pop‐in monitors (up to 200 mm) are regularly used for alignment and tuning of the various X‐ray optical components like mirrors, slits and monochromators, and also for on‐line beam control of a stable beam position at the instruments. The Exit Slit imager after the soft X‐ray monochromator provides spectral information of the beam together with multi‐channel plate based single‐pulse gating. For particular use cases, these special features of the imagers are described. Some radiation‐induced degradation of scintillators took place in this initial commissioning phase, providing useful information for better understanding of damage thresholds. Visible‐light radiation in the beam pipe generated by upstream bending magnets caused spurious reflections in the optical system of some of the imagers which can be suppressed by aluminium‐coated scintillating screens.